Transcriptional, biochemical, and histochemical response of resistant and susceptible cultivars of Brassica juncea against Albugo candida infection - Rai, Prajjwal; Prasad, Lakshman; Mehta, Samridhi; Yadav, Prashant; Sharma, Anubhuti; Mishra, Deep Narayan (Frontiers in Plant Science, 2024)
White rust disease caused by a biotrophic oomycete Albugo candida is one of the most serious impediments in realizing the production potential of Brassica juncea. Due to the obligate nature of the pathogen, R-gene-based resistance is unstable as the newer virulent races emerge quickly. For this, a deep understanding of the molecular basis of resistance is essential for developing durable resistant varieties. In this study, we selected one susceptible cultivar, ‘Pusa Jaikisan’ and its single R gene based resistant NIL, ‘Pusa Jaikisan WRR as the source of understanding the defense mechanism in B. juncea against A. candida. Comparative histochemical analysis at 12 dpi showed higher callose deposition in the resistant cultivar than in the susceptible which hints towards its possible role in defense mechanism. Based on the biochemical markers observation, total protein was found to have a negative correlation with the resistance. The antioxidant enzymes (POX, CAT, and SOD) and non-enzymatic ROS scavenging compounds such as polyphenols and proline showed a positive correlation with the white rust resistance. Polyphenol Oxidase (PPO) total chlorophyll and total carotenoids were also found to be more abundant in the ‘Pusa Jaikisan WRR’. Based on the heat map analysis, PAL was identified to be the comparatively most induced enzyme involved in the defense mechanism. The polyphenol oxidase, total chlorophyll and total carotenoids were also found to show higher activity in the ‘Pusa Jaikisan WRR’. Furthermore, to study the defense response of ‘Pusa Jaikisan WRR’ compared to ‘Pusa Jaikisan’ against A. candida infection, the gene expression analyses of salicylic acid (SA)-marker PR protein genes (PR1 and PR2) and jasmonic acid (JA)-marker PR protein genes (PR3 and PR12) were done by qRT-PCR. Based on the results, PR2 emerged as the best possible gene for defense against A. candida followed by PR1. PR3 and PR12 also showed positive correlation with the disease resistance which may be due to the JA pathway acting complementary to the SA pathway in case of B. juncea-A. candida interaction. This provides evidence for the JA-SA hormonal crosstalk to be synergistic in case of the white rust resistance.